Peran Kepala Sekolah Dalam Mengembangkan Sekolah Unggul Di Madrasah Ibtidaiyah Muhammadiyah Program Khusus Kartasura - Rohiima Haque, Anissa; , Risminawati, M.Pd (2017)
This study aims to describe (1) The role of the principal in the MI Muhammadiyah PK Kartasura in developing a superior school. (2) Obstacles in developing superior schools in MI Muhammadiyah PK Kartasura (3) Solutions to overcome barriers in developing superior schools in MI Muhammadiyah PK Kartasura. This type of research is qualitative. Data collection techniques used were interviews, documentation and observation. Data analysis techniques through data reduction steps, data presentation and conclusions. Data validity uses source triangulation and technique. The results of the research show that (1) the principal of MI Muhammadiyah PK Kartasura has been able to develop a superior school by applying managers well in managing excellent programs, managing good administration, establishing good relationships with the community, as leaders who can be role models, Supervision activities well. (2) Obstacles in developing schools to excel are the limited cost in developing facilities and infrastructure and lack of teacher experience. (3) The solution given by the principal is related to the lack of teacher experience that is with the program of teacher learning, apprenticeship in other better elementary schools and attending the seminar. The principal coordinates with the daily governing body (BPH) on the cost issue to develop school facilities and infrastructure.